Biological indices in water quality studies - Lee, Wing-woo; Pescod, M.B.; Htun, Maung Nay; Ouano, E.A.R.; Keidanren (Bangkok : Asian Institute of Technology, 1975)
The two indices of species diversity, namely, diversity index, d, derived from Information Theory and sequential comparison index, SCI, derived from Theory of Runs were studied by computer simulation and field studies. Artificial communities with different number of species, but same population size and distribution, were used to study the effect of species richness. Results showed that diversity index, d, is better in reflecting species richness. The study of the homogeneity of the two indices using artificial distributions with increasing skewness showed that sequential comparison index, SCI, is preferred to diversity index, d. Regression between 270 sets of values of d and SCI obtained from simulation gives a log- log correlation of 0.984. Field investigation employing benthic macro-invertebrates at 4 different sites showed that both d and SCI can reflect changes in water quality equally well in practice. It was found that community changes in benthic biota may be caused by pollution or other natural changes, and the absolute values of index values are not important, it is the relative changes of index values with respect to time or distance that reflects the environmental stresses. Field experience taught that visual examination of benthos usually gives some indication on the causes of changes.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Water quality; Biological specimens